2017
DOI: 10.1186/s13287-017-0554-x
|View full text |Cite
|
Sign up to set email alerts
|

The crosstalk between vascular MSCs and inflammatory mediators determines the pro-calcific remodelling of human atherosclerotic aneurysm

Abstract: BackgroundHuman mesenchymal stem cells (MSCs) possess well-known reparative abilities, but any defect of the immunomodulatory activity and/or the differentiation process may determine the development of human diseases, including those affecting the vascular wall. MSCs residing within the human aortic wall represent a potential cell mediator of atherosclerotic aneurysm development.MethodsMSCs isolated from healthy and aneurysm aortas were characterized by flow cytometer and tested for differentiation properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 36 publications
(39 reference statements)
1
27
0
Order By: Relevance
“…Interestingly, PPAR-γ is expressed in macrophage-foam cells in human and murine atherosclerotic plaques [26,27], as well as in human and mouse monocyte and macrophages. In parallel, our research data showed that a low expression of PPAR-γ in mesenchymal stromal cells (MSCs) isolated from human abdominal aortic atherosclerotic plaques; moreover, we demonstrated that stimulation with inflammatory cytokines TNF-α/IL-1β reduced PPAR-γ expression in healthy vascular MSCs [28]. These findings support the inverse relationship between PPAR-γ and the inflammatory process and imply a regulatory ability of PPAR-γ on immune system and inflammatory circuits.…”
Section: Functionssupporting
confidence: 71%
“…Interestingly, PPAR-γ is expressed in macrophage-foam cells in human and murine atherosclerotic plaques [26,27], as well as in human and mouse monocyte and macrophages. In parallel, our research data showed that a low expression of PPAR-γ in mesenchymal stromal cells (MSCs) isolated from human abdominal aortic atherosclerotic plaques; moreover, we demonstrated that stimulation with inflammatory cytokines TNF-α/IL-1β reduced PPAR-γ expression in healthy vascular MSCs [28]. These findings support the inverse relationship between PPAR-γ and the inflammatory process and imply a regulatory ability of PPAR-γ on immune system and inflammatory circuits.…”
Section: Functionssupporting
confidence: 71%
“…The vascular inflammation mobilizes the MSCs migration and adhesion in the gland or promotes the de novo MSCs proliferation due to the increased levels of pro-inflammatory cytokines, TGF-β or TNF-α. The crosstalk between vascular MSCs and inflammatory mediators, especially, interleukin-22, lead to MSCs proliferation, migration and osteogenic differentiation [ 266 , 267 ] under the influence of high levels of pineal melatonin and finally PGC formation. Brain tissue hypoxia : Many pathological conditions cause brain tissue hypoxia including hypertension, sleep apnea, stroke, and even respiratory disorders.…”
Section: Potential Mechanisms For Pgc Formationmentioning
confidence: 99%
“…AAA-MSCs were able to differentiate into endothelial-like cells, as demonstrated by the formation of a vascular network onto Matrigel and by the positivity to CD31 marker. Nevertheless, we observed a reduced expression of CD146, a pericyte marker, suggesting the instability and immaturity of the AAA-MSC-derived neo-vessels [37]. A representative image of AAA-MSC functional characteristics is reported in Figure 2.…”
Section: Functional Deregulation Of Mscs Within the Injured Arterymentioning
confidence: 84%
“…An aberrant differentiation program of MSCs can be crucial in triggering the complications of the atherosclerotic plaque, like ectopic bone formation, and represents the early stage during calcification process [40]. AAA-MSCs also exhibited a marked osteogenic ability, correlating with the vascular calcium levels as measured by angio-CT in the enrolled patients [37]. Thus, it can be postulated that MSCs are key players during the renewal as well as the pathological conditions affecting the vascular wall.…”
Section: Functional Deregulation Of Mscs Within the Injured Arterymentioning
confidence: 99%
See 1 more Smart Citation